2012
DOI: 10.1152/japplphysiol.00818.2012
|View full text |Cite
|
Sign up to set email alerts
|

Exercise training improves cardiac function and attenuates arrhythmia in CPVT mice

Abstract: Catecholaminergic polymorphic ventricular tachycardia (CPVT) is a lethal ventricular arrhythmia evoked by physical or emotional stress. Recessively inherited CPVT is caused by either missense or null-allele mutations in the cardiac calsequestrin (CASQ2) gene. It was suggested that defects in CASQ2 cause protein deficiency and impair Ca(2+) uptake to the sarcoplasmic reticulum and Ca(2+)-dependent inhibition of ryanodine channels, leading to diastolic Ca(2+) leak, after-depolarizations, and arrhythmia. To exami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 47 publications
0
11
0
Order By: Relevance
“…10 Regular exercise training has been shown to reduce the propensity for VT in a CASQ2 mutant CPVT2 mouse model. 11 Furthermore, results from mice with RyR2 dysfunction due to diabetic cardiomyopathy indicated that exercise training might improve RyR2 function through a CaMKIIdependent mechanism. 12 However, the therapeutic strategy that exercise directly reduces RyR2-dependent Ca 2+ leak in CPVT1 has never been shown before.…”
Section: Introductionmentioning
confidence: 99%
“…10 Regular exercise training has been shown to reduce the propensity for VT in a CASQ2 mutant CPVT2 mouse model. 11 Furthermore, results from mice with RyR2 dysfunction due to diabetic cardiomyopathy indicated that exercise training might improve RyR2 function through a CaMKIIdependent mechanism. 12 However, the therapeutic strategy that exercise directly reduces RyR2-dependent Ca 2+ leak in CPVT1 has never been shown before.…”
Section: Introductionmentioning
confidence: 99%
“…Our findings are in keeping with previous reports, which also showed that CPVT mice and human patients are able to perform moderate-intensity exercise. 6,10,11 In addition to absence of abnormal ventricular remodeling (Figure 3E), no difference in atrial weight, P-wave amplitude, and duration between SED and EX CASQ2 −/− mice indicates unaltered atrial structural and electrical remodeling after AIT (Figures 2A, 2B, and 3D, and Supplemental Table 1). 3 …”
Section: Discussionmentioning
confidence: 96%
“…CASQ2 Δ/Δ mice were implanted with a telemetry device (DSI St. Paul MM, device weight 3.8g) as previously described 14 . Provocation testing was performed at baseline and 15 min after IP drug injection of each drug (Table 1).…”
Section: Methodsmentioning
confidence: 99%
“…Proteins were extracted from frozen hearts and separated as previously described 14 . Electro-blotting to Hybond-C Extra membranes (Habersham, USA) was followed by incubation with rabbit anti-alpha 1 adrenergic receptor antibodies (1:400), (Acris Antibodies, Germany).…”
Section: Methodsmentioning
confidence: 99%